2011
DOI: 10.1523/jneurosci.3432-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Posttraining Ablation of Adult-Generated Neurons Degrades Previously Acquired Memories

Abstract: New neurons are continuously generated in the subgranular zone of the adult hippocampus and, once sufficiently mature, are thought to integrate into hippocampal memory circuits. However, whether they play an essential role in subsequent memory expression is not known. Previous studies have shown that suppression of adult neurogenesis often (but not always) impairs subsequent hippocampusdependent learning (i.e., produces anterograde effects). A major challenge for these studies is that these new neurons represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
124
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 63 publications
16
124
0
2
Order By: Relevance
“…Their reduced potential for being activated by glutamatergic inputs would impede their recruitment by training (Fig. S7D), preventing their contribution to long-term spatial memory (44). Our previous studies in zif268-KO mice have shown that zif268 is required for the expression of late-phase hippocampal LTP (25), long-term stability of hippocampal place cell representations (31), and consolidation of several forms of long-term memory (25,28).…”
Section: Discussionmentioning
confidence: 94%
“…Their reduced potential for being activated by glutamatergic inputs would impede their recruitment by training (Fig. S7D), preventing their contribution to long-term spatial memory (44). Our previous studies in zif268-KO mice have shown that zif268 is required for the expression of late-phase hippocampal LTP (25), long-term stability of hippocampal place cell representations (31), and consolidation of several forms of long-term memory (25,28).…”
Section: Discussionmentioning
confidence: 94%
“…Adult neurogenesis is required for contextual discrimination, spatial memory, and spatial pattern separation (Clelland et al 2009;Arruda-Carvalho et al 2011;Sahay et al 2011;Denny et al 2012;Nakashiba et al 2012;Niibori et al 2012; see Abrous and Wojtowicz 2015 for in-depth discussion). A role for adultborn neurons in relation to emotion was first proposed with the observation that changes in adult neurogenesis correlate with mood-related manipulations in both negative (Gould et al 1992) and positive directions (Malberg et al 2000;van Praag et al 2002) (especially in the temporal DG).…”
Section: Functional Rolesmentioning
confidence: 99%
“…Recent studies looking at the effect of post-training ablation (retrograde effects) of newborn neurons and silencing of adult-generated neurons on hippocampal memory further highlight the importance of this neuronal population in formation of memory. Ablation of newborn neurons using a diphtheria toxinbased strategy after learning leads to degradation of existing contextual fear and water maze memories, even when the ablation is induced 1 month after learning (Arruda-Carvalho et al 2011). Along the same line, using an optogenetic approach, it has been shown that silencing newborn neurons affects the retrieval of memory after completion of training.…”
Section: The Role Of Hippocampal Neurogenesis In Cognitionmentioning
confidence: 99%